Paired Exchange Living Donor Liver Transplantation: A Nine-year Experience From North India. Issue 11 (30th June 2022) - Agrawal, Dhiraj; Saigal, Sanjiv; Jadaun, Shekhar Singh; Singh, Shweta A.; Agrawal, Shaleen; Gupta, Subhash
Abstract : Background: Paired exchange liver transplantation is an evolving strategy to overcome ABO blood group incompatibility and other barriers such as inadequate graft-to-recipient weight ratio and low remnant liver volume in donors. However, for the transplant team to carry 4 major operations simultaneously is a Herculean effort. We analyzed our experience with liver paired exchange (LPE) program over the past 9 y. Methods: This prospective study included 34 of 2340 (1.45%) living donor liver transplantations performed between May 2012 and April 2021. The reason for LPE was ABO incompatibility in all (n = 34) patients included in the study. After donor reassignment through 2-by-2 paired exchange with directed donors, the ABO matching status changed from A to A (n = 17) and B to B (n = 17), which made all matches ABO-identical. Recipients (R) and donors (D) of each swap pair were prospectively divided into R1/D1 and R2/D2 groups for comparative and survival analyses. Results: The recipients (n = 34) had a median age of 45.5 y (11–59 y), and 31 were men. LPEs were performed in 4 operating rooms running simultaneously by 2 independent surgical teams. Donor survival was 100%. Baseline clinical and perioperative parameters, postoperative complications, median intensive care unit/hospital stay, and early deaths were comparable ( P > 0.1) between the R1 and R2 groups. The median follow-up period was 27 mo (1–108 mo). The 30-d and 1-y survivals were 88.2% (n = 30) and 85.3% (n = 29), respectively. Conclusions: Our experience suggests that with careful attention to ethical and logistical issues, the LPE program can expand the living donor liver pool and facilitate a greater number of living donor liver transplantations. Abstract :